“FOLDING BODIES”: THE HISTORY OF CHIKUNGUNYA EPIDEMICS AND OUTBREAKS IN BRAZIL. (Fiep Bulletin - online, 2020)
The aim of this paper is to analyze the history of chikungunya epidemics and outbreaks in Brazil. Outbreaks and epidemics reported by the national press that becomes the main vehicle for disseminating information about the disease. Knowledge about the chikungunya virus is now structured by the media. In this sense, it is essential to evaluate the agreements and disagreements of this translation. Chikungunya is known in Africa as the disease of "those who bend," an allusion to the curved appearance of patients who could not lift their bodies because of characteristic joint pain. In 2014, 824 cases of chikungunya were recorded in Brazil. Chikungunya outbreaks in the southeastern region occur from 2015. It becomes epidemic in northeastern Brazil in mid-2016. With 60,000 confirmed cases of chikungunya in Ceará that had so far the highest rate in the country. Chikungunya in its most acute phase compromises the joints promoting severe pain and sequelae that can last up to six months. It is suspected that chikungunya virus may lead the individual to develop another condition known as Guillain Barré syndrome, autoimmune disease.“Bending bodies” for a longer period can produce incapable bodies for good. Historical mapping of chikungunya epidemics and outbreaks may provide some important tools for assessing the current picture of the disease